Development of a comet-FISH assay for the detection of DNA damage in hemocytes of Crassostrea gigas - Perez Garcia, Maria Concepcion; Rouxel, Julien; Akcha, Farida (Aquatic Toxicology, 2015)
In this work, the DNA-damaging effect of hydrogen peroxide on the structural integrity of nucleolar organizer regions (NORs) was studied for the first time by comet-FISH in the Pacific oyster Crassostrea gigas. Global DNA damage was assessed in hemocytes using an alkaline version of the comet assay. Next, NOR sensitivity was analysed by mapping major rDNA repeat unit by fluorescence in situ hybridisation (FISH) on the same comet slides. Exposure of hemocytes to 100 μM of hydrogen peroxide induced a significant increase in both DNA damage and number of FISH-signals of major ribosomal genes versus the control. Moreover, a significant positive correlation was shown between DNA damage as measured by the comet assay (percentage of DNA in comet tail) and the number of signals present in comet tails. This study demonstrates the potential value of the comet-FISH assay for the study of DNA damage induced by genotoxicant exposure of target genes. It offers a perspective for better understanding the impact of genotoxicity on animal physiology and fitness.